A Prestação de Serviços Ambientais pode ser uma alternativa aos sistemas tradicionais da agricultura familiar no município de Pacajá, Amazônia Paraense ”“ Brasil? (Sustainability in Debate, 2013)
The majority of smallholder farms adopt traditional systems of agriculture using an area for one or two years and then left fallow. This production model in the Amazon has been identified by some as a social problem and ecological villain. Counterpoint to this view, it is understood that smallholder farming is strategic in maintaining employment, income redistribution, ensuring the country’s food sovereignty and sustainable alternative development, given that the diversification of production systems and characteristics balance the relationship between man and nature. In the text, we propose reflection on the Provision of Environmental Services in the municipality of Pacajá in the State of Para, Brazil. We adopted the Eco-Cert tool and the PROAMBIENTE project, developed by Embrapa, to identify the practices that contribute to the services. Results show that diversification is key to providing environmental services and that the families that participate of PROAMBIENTE increased the potential in providing services, especially for not clearing the forests and reducing the use of fire.